DNA methylation‐mediated inhibition of MGARP is involved in impaired progeny testosterone synthesis in mice exposed to DBP in utero. Issue 4 (5th January 2023) - Li, Huan; Jiang, Yutong; Liu, Minhui; Yu, Jiaxin; Feng, Xinyue; Xu, Xiaolei; Wang, Hongyan; Zhang, Jing; Sun, Xiuling; Yu, Yan
Abstract: The dibutyl phthalate (DBP) has been detected in fetuses and infants and can cause damage to the reproductive system in adulthood, but the exact mechanism remains unclear. Here, we aim to investigate the effects of intrauterine DBP exposure on offspring reproductive function and explore possible mechanisms. SPF C57BL/6 pregnant mice were given DBP (0.5, 5, 75 mg/kg/d) or corn oil from day 5 to day 19 by gavage. After weaning, the pups were fed a standard diet for 5 weeks. In addition, TM3 Leydig cell cultures were used to study the relevant mechanisms in vitro . The results showed that intrauterine DBP exposure could reduce sperm density and sperm motility, cause testicular tissue damage, down‐regulate serum T and LH levels, and up‐regulate serum FSH levels at 75 mg/kg/d. Western blot and methylation detection revealed intrauterine exposure to DBP down‐regulated testosterone synthesis‐related proteins StAR, P450scc, 3β‐HSD, PKA, and PKC expression, while up‐regulated the levels of methyltransferase proteins expression and DNA 5‐methylcytosine (5mC) in testicular tissue of mouse offspring at 75 mg/kg/d. Further detection found in utero 75 mg/kg/d DBP exposure down‐regulated MGARP protein expression, and induced incomplete methylation of the MGARP gene. An in vitro analysis showed that MGARP inhibition is involved in an impaired testosterone synthesis in TM3 cells. Cell culture results suggest that MGARP down‐regulation may be involved in impaired testosterone production in monobutyl phthalate‐treated cells. The present study revealed that 75 mg/kg/d DBP exposure in utero resulted in testosterone synthesis disorders and reproductive function impairment in mouse offspring, and the mechanism may be related to DNA methylation‐mediated down‐regulation of MGARP in the testis.